A Systematic Review of European Clinical Practice Guidelines for Respiratory Syncytial Virus Prophylaxis. (25th March 2022) - Reeves, Rachel M; van Wijhe, Maarten; Lehtonen, Toni; Stona, Luca; Teirlinck, Anne C; Vazquez Fernandez, Liliana; Li, You; Osei-Yeboah, Richard; Fischer, Thea K; Heikkinen, Terho; van Boven, Michiel; Bøås, Håkon; et al.
Abstract: Background: Since the widespread adoption of palivizumab prophylaxis in Europe, there have been a number of clinical practice guidelines (CPGs) published for the prevention of respiratory syncytial virus (RSV) infection in children. The aim of this systematic review was to identify CPGs for the prevention of RSV infection across Europe. Methods: We performed a systematic literature search and contacted European influenza and respiratory virus networks and public health institutions, to identify national CPGs for the prevention of RSV infection. The Reporting Items for practice Guidelines in Healthcare (RIGHT) Statement checklist was applied to extract data and review the quality of reporting. Results: A total of 20 national CPGs were identified, all published between 2000 and 2018. The greatest discrepancy between guidelines was the recommendations for palivizumab prophylaxis for premature infants, with recommendations varying by gestational age. All guidelines recommended or considered the use of palivizumab in infants with bronchopulmonary dysplasia, 85% (n = 17) in children with congenital heart disease (CHD), and 60% (n = 12) in children with severe combined immunodeficiency. Conclusions: We recommend that agencies publishing RSV prevention guidelines adopt the RIGHT reporting requirements when updating these guidelines to improve the presentation of the evidence-base for decisions.